Evaluation of personal, socioeconomic and psychological characteristics of FFS and non-FFS groundnut growers: EVALUATION OF FFS AND NON-FFS GROUNDNUT GROWERS - S SREENIVASULU; P K JAIN; T P SASTRY (Journal of Oilseeds Research, 2014)
The personal, socioeconomic and psychological characteristics play a vital role in planning any capacity building programmes to farmers. A study was conducted during 2012-13 to know the personal, socioeconomic and psychological characteristics of Farmer Field School (FFS) and non-FFS farmers of groundnut in Chittoor district of Andhra Pradesh. There was no significant difference in farming experience and socioeconomic status was observed between FFS and non-FFS farmers of groundnut. Significant differences in extension participation, mass media exposure, innovativeness, achievement motivation, management orientation, economic orientation, information input behavior, information process behaviour and information output behaviour were observed between FFS and non-FFS farmers of groundnut.